Psychogenic nonepileptic seizures: an overview - De Paola,Luciano (2007)
Pyschogenic nonepileptic seizures (PNES) are common and potentially harmful - both physically and emotionally - events. They are often under or misdiagnosed. Not only neurologists managing epilepsy, but also generalists and ER physicians should be aware of its existence, preventing unnecessary tests, as well as, iatrogenic interventions. The assistance provided to these patients is often inadequate, even at larger and busier epilepsy centers. That clearly impacts on the prognosis of this condition, which is fairly difficult to manage per se, yet with the best possible quality of care, including well trained multiprofessional teams.